2007
DOI: 10.1074/jbc.m703896200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Carboxysomes from Synechococcus PCC7942 Reveals Multiple Rubisco Complexes with Carboxysomal Proteins CcmM and CcaA

Abstract: In cyanobacteria, the key enzyme for photosynthetic CO 2 fixation, ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), is bound within proteinaceous polyhedral microcompartments called carboxysomes. Cyanobacteria with Form IB Rubisco produce ␤-carboxysomes whose putative shell proteins are encoded by the ccm-type genes. To date, very little is known of the protein-protein interactions that form the basis of ␤-carboxysome structure. In an effort to identify such interactions within the carboxysomes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
227
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(241 citation statements)
references
References 51 publications
13
227
1
Order By: Relevance
“…Only 4 of our 20 strains contained both ccaA and ccaA2. The amino-acid sequence of CcaA2 is slightly shorter than CcaA, and the two different isoforms might enable cells to modify their CO 2 fixation efficiency (Long et al, 2007), although further confirmation of this hypothesis is warranted.…”
Section: Ccm Genes Of Microcystismentioning
confidence: 98%
“…Only 4 of our 20 strains contained both ccaA and ccaA2. The amino-acid sequence of CcaA2 is slightly shorter than CcaA, and the two different isoforms might enable cells to modify their CO 2 fixation efficiency (Long et al, 2007), although further confirmation of this hypothesis is warranted.…”
Section: Ccm Genes Of Microcystismentioning
confidence: 98%
“…32 How the interior of the carboxysome is organized relative to the shell is understood only in rough terms. 23,24 Two recent studies have highlighted the role of the CcmM protein in the b-type carboxysome in binding several other carboxysome proteins, 28,29 including the CcmK shell proteins. 29 The structural details of these interactions have not been illuminated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent studies on b-caboxysomes suggest that the CcmM protein plays a key organizing role. 28,29 In one study, 29 yeast two hybrid experiments showed direct interactions between CcmM and the CcmK (BMC-type) shell proteins under study in the present work. The atomic level details of those interactions have not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Its shell is assembled from roughly 800 protein hexamers, which form the facets of the icosahedron, and 12 pentamers, which form the vertices (8,12). Inside the lumen are the enzymes ribulose 1,5-bisphosphate carboxylase/oxygenase (RuBisCO) and carbonic anhydrase (CA), which are directed to this location by protein-protein interactions with the shell and/or shell interaction mediators (13). Depending on the organism, genes for these shell proteins and luminal enzymes can occur either together in a single operon or, alternatively, in several operons across the genome (9).…”
mentioning
confidence: 99%